Transfer pricing practises of intensive advertising, marketing and promotion expense in Indonesia: case study in PT Z / Punia Mega Metlissa and Nanda Ayu Wijayanti - Metlissa, Punia Mega; Wijayanti, Nanda Ayu (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
This study aims to understand the phenomenon in determining and assessing marketing intangible that arise from advertising, marketing, and promotion expense (AMP expense). Marketing activities usually raise AMP expense for the company. According to Darussalam, Septriadi, and Kristiaji (2013) marketing intangible can cause transfer pricing problems in terms of marketing expenses carried out by unbranded parties in multinational companies. These problems arise because of the difficulty in identifying marketing intangible, determining the owner and assessing marketing intangible remuneration appropriately (Fedi, 2019). This caused different assessment of marketing intangible between taxpayer and tax authority. This study used qualitative research with case study in PTZ, a distributor who sales products whose brand are owned by affiliate. Based on the interviews, the results show that AMP expenses can create marketing intangible when a company pays royalties for the use of intangible marketing to affiliation (such as the use of trademarks, brands, etc.) and the AMP expense are quite large in excess of the comparison company. The ownership of intangible marketing is carried out through a function, asset and risk analysis that focuses on the development, improvement, maintenance, protection and exploitation (DEMPE) of intangible assets (OECD, 2017). Marketing intangible remuneration can be given in the form of a reduction in the purchase price, direct compensation for expenses that exceed the expenses of an independent party plus profits based on the functions and risks borne (OECD, 2017). Currently, Indonesia does not has special provisions related to the issue of AMP expense that can create marketing intangibles, so this guidance is expected to help identifying, determining ownership and assessing remuneration for marketing intangible expenses arising from AMP expense.